Immune Reactions in the Body Based on Listeriosis. (Eurasian Medical Research Periodical, 2022)
The review presents data on the antigenic structure of Listeria and the modern classification of epidemically significant Listeria serovariants. Information is given on the characteristic species-specific properties of Listeria serovariants, which may be common to two or more species, and also have common antigens with staphylococci, typhoid-paratyphoid bacteria.